HUBUNGAN ANTARA PERAN DOSEN PEMBIMBING DENGAN KECEMASAN MAHASISWA KEPERAWATAN DALAM MENGHADAPI TUGAS AKHIR SKRIPSI DI PERGURUAN TINGGI 2014 - Karyanah, Yayah (Indonesian Journal of Nursing Health Science, 2016)
AbstractVarious problems faced by students in the Nursing ProgramÂ  face final thesis. So that it is the trigger anxiety in the face thesis student thesis. Anxious in the face of the thesis for fear of lecturers, lecturers who are difficult to find, and the lecturers is too easy in the guidance. This study aims to examine the correlation between lecturers role with the anxiety level of students to face the final project (thesis). The variables of this study is the role of independent sebagai.variabel lecturers and student anxiety levels as the dependent variable. The study population is students of nurses Esa Unggul University last semester Academic Year 2014-2015 Odd. Total population 40 students. All the population sampled. The sampling technique is saturated sample. Analytical descriptive research method with cross sectionals. Results obtained The role of the supervisor is active 36 (90%). The role of the lecturer is not active 4 (10%). Research on anxiety found 21 (52.5%) students do not experience anxiety, 4 .students mild anxiety level, three students suffered anxiety level was 8 students experiencing severe anxiety and 4 heavy level. Statisstk test with Chi-Square. Statistical test result p value 0.001 <0.05 .: There is a relationship between the role of Supervisor and Anxiety Levels in the Final Semester Students Facing the final project (thesis) at universities.Â Keywords: Role, Supervisor, Anxiety